First feedback-controlled divertor detachment in W7-X: Experience from TDU operation and prospects for operation with actively cooled divertor. (March 2023) - Krychowiak, M.; König, R.; Barbui, T.; Brezinsek, S.; Brunner, J.; Effenberg, F.; Endler, M.; Feng, Y.; Flom, E.; Gao, Y.; Gradic, D.; Hacker, P.; et al.
Abstract: In the last experimental campaign (OP1.2b) of the stellarator Wendelstein 7-X (W7-X), boronisation as a mean for first wall conditioning was applied for the first time which led to strongly reduced impurity fluxes from plasma-facing components. Thermal detachment at the uncooled target plates of the test divertor unit (TDU) was reached at higher plasma densities and was accompanied by high recycling of neutrals at the target plate [1], [2] . A feedback control system was established in W7-X to actively control the gas injection (actuator) for plasma fuelling and impurity seeding [3] through the divertors. It allowed very successful stabilisation of the detached plasma condition state as well as mitigation of thermal overloads to some baffle tiles. Different routinely available diagnostic signals were used as input parameters (sensors). We describe the setup of the feedback control system, its performance and provide some example results with the main focus on the development of the control scheme which led to the detachment stabilisation over the entire longest (30 s) high-power discharge at W7-X so far. In view of the achieved very successful detachment stabilisation and the necessity to include simultaneous optimisation of the core performance in the future, the feedback control system is being upgraded for the upcoming campaign (OP2.1) in which the water cooled and hereby inherently steady-state capable divertor has been currently installed. The prospects and some experiment ideas for active detachment control are discussed. Highlights: First feedback-controlled divertor detachment in W7-X. Pre-optimisation of PID controller parameters in a lab simulation setup. Stabilisation of detached plasma conditions over 30 s of plasma discharge. Mitigation of excessive heat loads to baffles by feedback control of total radiated power.